'Backstabbed by a Friend and Saved by an Enemy': Narratives of War: The Gulf War in Saudi Oral Histories. (8th July 2021) - Winkel, Carmen
Abstract : The Gulf War (1990–1991) had a transformative effect on Saudi Arabia and its society. The war brought major ideological changes and allowed its citizens for the first time to voice critique and concern about economic and social problems. Many studies have highlighted the diverse reactions and dilemmas of Saudi people from the crumbling notion of Arab unity to the emergence of the United States to stop the looming invasion of the Iraqi leader Saddam Hussein. Although there is a plethora of studies about the Gulf War, none of them has investigated how ordinary Saudi citizens experienced the war with all its implications. The paper describes what narratives were used by interviewees in oral history interviews when talking about the war and its effect on their lives, families, and worldview.